Does IT Matter? Has Technology Failed To Influence Competition at The Firm Level? Another Dimension to IT Investments and Firm Performance - Andoh, Emilyn (2006)
Corporations stand at the threshold of a new age. Confronted with worldwide turbulence and competition, information technology is the new weapon that is capable of dramatically changing the balance of power. An effective battle plan and the ability to mobilize resources are essential.